Apartheidideologi og materiell kultur - Gilje, Nils (Tidsskrift for kulturforskning, 2007)
The article discusses some of the controversies related to the Voortrekkermonument located on the hills south of Pretoria (Tswane) in South Africa. The monument was inaugurated in 1949 during the installation of the new apartheid regime. For many years it was celebrated as an icon of apartheid and was used by the National Party and extreme right wing groups honoring Afrikaner history and the politics of apartheid. The presence of an apartheid ideology in the historical friezes in the Hall of Heroes is, however, not obvious. The presentation of the wars between the Boers and the Ndebele and Zulus does not necessarily represent the ideology and politics of apartheid. The complete absence of the so-called "colored" population in the friezes may, on the other hand, be interpreted as a sign of apartheid. This makes it difficult to see how the Voortrekkermonument successfully can become part of the national cultural heritage of the new, democratic South Africa.